Trends in Survival of Patients with Primary Gastric Diffuse Large B-Cell Lymphoma: An Analysis of 7051 Cases in the SEER Database. (16th October 2018) - Liu, Pan-pan; Xia, Yi; Bi, Xi-wen; Wang, Yu; Sun, Peng; Yang, Hang; Li, Zhi-ming; Jiang, Wen-qi
Abstract : Treatment modalities for primary gastric diffuse large B-cell lymphoma (PG-DLBCL) have changed significantly during the past decades. However, limited information on the trends of clinical outcome of PG-DLBCL patients has been reported. Here, we conducted a retrospective analysis using the Surveillance, Epidemiology, and End Results (SEER) database to compare the survival trends of PG-DLBCL patients from 1973 to 2014. Patients were divided into 2 eras based on the year of diagnosis in relation to immunotherapy with the anti-CD20 antibody rituximab that was approved in 1997 and became a widely used drug in 2000. There was a significant improvement in survival among PG-DLBCL patients diagnosed in the 2001–2014 era (n = 4186 ) compared to patients diagnosed in the 1973–2000 era (n = 2865 ), with the 5-year overall survival rates of 53% and 47%, respectively (p = 0.001 ). Multivariable analysis revealed that the 2001–2014 era (HR = 0.892, p = 0.001 ) was associated with lower mortality and that patients of older age, Black race, advanced stage, and male gender were associated with poor prognosis. Although outcome of PG-DLBCL has significantly improved over time, more effective therapies are needed for older patients to further improve their survival.